Evaluation of antibacterial efficacy of some alcohol-based hand sanitizers sold in Ilorin (north-central Nigeria) - Oke, M.A.; Bello, A.B.; Odebisi, M.B.; Ahmed El-Imam, A.M.; Kazeem, M.O. (Faculty of Science Obafemi Awolowo University, Ile-Ife, Nigeria, 2013)

(untitled)
Hospital and community-acquired infections are a serious problem worldwide often leading to increased deaths, costs and other problems. Hand hygiene has been promoted as the most important way to prevent these infections. The use of hand sanitizers is one of the ways to address the barriers to effective hand hygiene. In this study, we evaluated the antibacterial efficacy of some popular hand sanitizers sold in Ilorin. The well-variant of the agar diffusion test was used to evaluate the efficacy of the products against Staphylococcus aureus, Streptococcus pneumoniae, Escherichia coli, Pseudomonas aeruginosa and Klebsiella pneumoniae. Hygel alone inhibited all the test organisms with zones of inhibition ranging between 14.3mm and 28.0mm while Dettol was only effective against P. aeruginosa (14.5mm). The other products (SKP and Samcleans) were not active against any of the test organisms. Hygel and Dettol were bacteriostatic at 100% concentration (MIC) and none was bactericidal. In vivo tests to determine the efficacy of these two in reducing bacterial counts from hands of subjects showed mean percentage cfu reduction of 89.9% for Hygel and 73.8% for Dettol. There was no significant difference in the efficacy of the two products in this regard. Despite the claims of efficacy and 99.9% bacterial count reduction by hand sanitizer manufacturers, there still exists a need for verification of these claims by regulatory bodies and for the enforcement of good quality control measures.